A one dimensional mathematical model for urodynamics - Celik, Ismail B.; Bayrak, Coskun; Varol, Asaf; Nanduri, Jagannath R. (My University, 2007)
Millions of people in the world suffer from urinary incontinence and overactive bladder with the major causes for the symptoms being stress, urge, overflow and functional incontinence. For a more effective treatment of these ailments, a detailed understanding of the urinary flow dynamics is required. This challenging task is not easy to achieve due to the complexity of the problem and the lack of tools to study the underlying mechanisms of the urination process. Theoretical models can help find a better solution for the various disorders of the lower urinary tract, including urinary incontinence, through simulating the interaction between various components involved in the continence mechanism. Using a lumped parameter analysis, a one-dimensional, transient mathematical model was built to simulate a complete cycle of filling and voiding of the bladder. Both the voluntary and involuntary contraction of the bladder walls is modeled along with the transient response of both the internal and external sphincters which dynamically control the urination process. The model also includes the effects signals from the bladder outlet (urethral sphincter, pelvic floor muscles and fascia), the muscles involved in evacuation of the urinary bladder (detrusor muscle) as well as the abdominal wall musculature. The necessary geometrical parameters of the urodynamics model were obtained from the 3D visualization data based on the visible human project. Preliminary results show good agreement with the experimental results found in the literature. The current model could be used as a diagnostic tool for detecting incontinence and simulating possible scenarios for the circumstances leading to incontinence. Copyright © 2007 by ASME.
2007 5th Joint ASME/JSME Fluids Engineering Summer Conference, FEDSM 2007 -- 30 July 2007 through 2 August 2007 -- San Diego, CA -- 71514
Keywords: Biological organs; Computer simulation; Fluid dynamics; Mathematical models; Abdominal wall musculature; Urinary incontinence; Urodynamics; Biomedical engineering